The effective management of teachers’ habitual tardiness: Protecting scheduled teaching time - Michael Moreti Mahome; Lydia Kgomotso Mphahlele (International Journal of Educational Management and Development Studies)
Teachers’ habitual tardiness poses the most problem to school managers anywhere in the world and has countless drawbacks. It is one of the main anomalies that have beset many South African public schools, deplorably substantial emphasis has been given to teachers’ absenteeism. Espousing a qualitative research approach, coupled with multiple case study design, this enquiry aimed to explore how School Management Teams (SMTs) effectively manage teachers’ habitual tardiness and come up with strategies to protect scheduled teaching time. Data was collected through face-to-face interviews and the review of documents. Data was analysed with the employment of Inductive Thematic Analysis (ITA) method embedded within the moral leadership framework. The purposefully selected sample comprised seven SMT members from three public secondary schools in Soshanguve township, South Africa. The findings revealed that habitual tardiness by same teachers is a problem in all the three schools, whereby missing the first period was a daily occurrence. The findings further painted a bleak picture on the scheduled teaching time that is lost and usually unaccounted for. To effectively manage habitual tardiness, school managers are advised to implement and monitor the tardiness attendance register. It is further recommended that a roundtable discussion be held amongst basic education stakeholders for the introduction of the biometric log-in system. To protect scheduled teaching time, the streamlining of the school timetable is proposed.